2016
DOI: 10.1016/j.biocel.2016.08.044
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-inflammatory actions of (−)-epicatechin in the adipose tissue of obese mice

Abstract: Obesity and type 2 diabetes (T2D) are major public health concerns. Visceral adipose tissue inflammation is considered a significant contributor to obesity-associated T2D development. We previously showed that the flavan-3-ol (−)-epicatechin (EC) can mitigate insulin resistance in mice fed a high fat diet (HFD). This study investigated the capacity of EC to inhibit visceral adipose tissue inflammation occurring as a consequence of HFD consumption in C57BL/6J mice, and characterized the underlying mechanisms. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 51 publications
8
38
0
1
Order By: Relevance
“…Comparable anti-inflammatory actions have been previously reported in several in vivo models of endotoxemia when using flavonoid-rich plant extracts, as well as for isolated flavonoids or their metabolites [25], [26], [27], [28], [29]. Regarding the actions of ( − )-epicatechin, we have previously reported that in fructose-fed and in high fat-fed rats inflammatory markers were mostly normalized by the presence of (−)-epicatechin in the diet [30], [31]. Then, the present results are confirmatory of an anti-inflammatory action of (−)-epicatechin, in this case associated with improved kidney function.…”
Section: Discussionsupporting
confidence: 48%
“…Comparable anti-inflammatory actions have been previously reported in several in vivo models of endotoxemia when using flavonoid-rich plant extracts, as well as for isolated flavonoids or their metabolites [25], [26], [27], [28], [29]. Regarding the actions of ( − )-epicatechin, we have previously reported that in fructose-fed and in high fat-fed rats inflammatory markers were mostly normalized by the presence of (−)-epicatechin in the diet [30], [31]. Then, the present results are confirmatory of an anti-inflammatory action of (−)-epicatechin, in this case associated with improved kidney function.…”
Section: Discussionsupporting
confidence: 48%
“…Interestingly, both studies outlined increased oxidative stress and inflammation in these two different models of metabolic syndrome and their reduction following epicatechin supplementation. The authors propose a mechanism involving the reduction of oxidative stress, the consequent reduction of NF‐κB activation and of adipose tissue inflammation . Therefore, our results seem to confirm that, the positive effects of flavan‐3‐ol consumption on BAT may be secondary to a decreased oxidative stress which in turns might trigger a reduced inflammatory status.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, Bettaieb et al . demonstrated both in high fructose‐fed rats and high fat diet‐fed mice , the capacity of epicatechin supplementation to alleviate metabolic syndrome and adipose tissue inflammation and dysfunction. Interestingly, both studies outlined increased oxidative stress and inflammation in these two different models of metabolic syndrome and their reduction following epicatechin supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental and clinical studies, inflammatory markers such as C-reactive protein, tumor necrosis factor-alpha, interleukin 6 and nu-clear factor kappa-␤, are associated with lipids level [39]. EC has been shown to reduce chronic inflammation in various animal models and under various conditions [17,[40][41][42][43][44]. In current study, EC was found to significantly reduce IL-1beta, IL-2 and IL-6 in hyperlipidemic rats, with is in line with previous reports.…”
Section: Discussionmentioning
confidence: 99%